Postural Control in Children with Dyslexia: Effects of Emotional Stimuli in a Dual‐Task Environment. (4th July 2017) - Goulème, Nathalie; Gerard, Christophe‐Loïc; Bucci, Maria Pia
Abstract : The aim of this study was to compare the visual exploration strategies used during a postural control task across participants with and without dyslexia. We simultaneously recorded eye movements and postural control while children were viewing different types of emotional faces. Twenty‐two children with dyslexia and twenty‐two aged‐matched children without dyslexia participated in the study. We analysed the surface area, the length and the mean velocity of the centre of pressure for balance in parallel with visual saccadic latency, the number of saccades and the time spent in regions of interest. Our results showed that postural stability in children with dyslexia was weaker and the surface area of their centre of pressure increased significantly when they viewed an unpleasant face. Moreover, children with dyslexia had different strategies to those used by children without dyslexia during visual exploration, and in particular when they viewed unpleasant emotional faces. We suggest that lower performance in emotional face processing in children with dyslexia could be due to a difference in their visual strategies, linked to their identification of unpleasant emotional faces. Copyright © 2017 John Wiley & Sons, Ltd.